Prince Avalanche [videorecording (DVD)] - Green, David Gordon, 1975-; Green, David Gordon, 1975-; Rudd, Paul; Hirsch, Emile, 1985-
An odd couple of sorts, introspective and stern Alvin and his girlfriend's brother, Lance, dopy and insecure, leave the city behind to spend the summer of 1988 repainting traffic lines on a desolate country highway where the surrounding areas have been ravaged by wildfire. The men bicker and joke with each other, eventually developing an unlikely friendship.